Enhanced charge collection with passivation of the tin oxide layer in planar perovskite solar cells. Issue 25 (14th June 2017) - Lee, Yonghui; Paek, Sanghyun; Cho, Kyung Taek; Oveisi, Emad; Gao, Peng; Lee, Seunghwan; Park, Jin-Seong; Zhang, Yi; Humphry-Baker, Robin; Asiri, Abdullah M.; Nazeeruddin, Mohammad Khaja
Abstract : The morphological, opto-physical and electrical properties of the SnO2 layer in perovskite solar cells are investigated. Abstract : Tin oxide is an excellent candidate to replace mesoporous TiO2 electron transport layers (ETLs) in perovskite solar cells. Here, we introduced a SnO2 layer by a low-temperature solution process, and investigated its morphology, opto-physical and electrical properties affecting the device performance. We reveal that low-temperature processed SnO2 is self-passivating in nature, which leads to a high efficiency. To further enhance the blocking effect, we combined a compact TiO2 underlayer with the SnO2 contact layer, and found that the bi-layered ETL is superior compared to single layers. The best device shows photovoltaic values in a planar structure with a short-circuit current density ( J sc ) of 22.58 mA cm −2, an open-circuit voltage ( V oc ) of 1.13 V, a fill factor (FF) of 0.78, and a power conversion efficiency (PCE) of 19.80% under 1 sunlight illumination.